Sun-Drying and Melatonin Treatment Effects on Apricot Color, Phytochemical, and Antioxidant Properties - Rukiye Zengin; Yılmaz Uğur; Yasemin Levent; Selim Erdoğan; Harlene Hatterman-Valenti; Ozkan Kaya (Applied Sciences)
Post-harvest deterioration of fruit quality represents a significant challenge in the dried fruit industry, particularly affecting the preservation of nutritional compounds and sensory attributes during the drying process. This research examined the potential protective effects of exogenous melatonin supplementation on the preservation of selected quality metrics and antioxidant characteristics in sun-dried apricots, utilizing a comparative analysis across disparate melatonin concentrations (10, 100, and 1000 µM). Our research findings demonstrated that melatonin treatment, particularly at 100 µM concentration, significantly enhanced quality preservation in sun-dried apricots. Specifically, the treatment resulted in improved color retention (increased L*, a*, and b* values), reduced oxidative stress markers (MDA and H2O2), and optimized sugar composition (glucose: 18.99 g/100 g, fructose: 12.58 g/100 g, sucrose: 15.52 g/100 g). The melatonin treatment at 100 µM concentration proved particularly effective, revealing the most significant results. Specifically, this concentration resulted in the highest β-carotene levels, reaching 223.07 mg/kg. These findings suggest promising applications for commercial-scale implementation through either dipping or spraying methods. The non-toxic nature of melatonin and its demonstrated efficacy in preserving fruit quality parameters position it as a valuable post-harvest treatment option in the fruit supply chain. This research contributes significantly to advancing sustainable post-harvest preservation strategies, though further investigation into melatonin stability and standardization of application protocols remains necessary for optimal commercial implementation.